4-Methyl-N-p-tolylpiperidine-1-carboxamide - Li, Yu-Feng (International Union of Crystallography, 2012)
In the title molecule, C(14)H(20)N(2)O, the piperidine ring has a chair conformation and its N atom is close to planar (bond-angle sum = 357.5°). The dihedral angle between the amide group and the aromatic ring is 47.43 (19)°. In the crystal, molecules are linked into [100] C(4) chains by N—H⋯O hydrogen bonds.